Emerging targets of α-synuclein spreading in α-synucleinopathies: a review of mechanistic pathways and interventions - Grace Kuo; Ramhari Kumbhar; William Blair; Valina L. Dawson; Ted M. Dawson; Xiaobo Mao (Molecular Neurodegeneration)
Abstract α-Synucleinopathies constitute a spectrum of neurodegenerative disorders, including Parkinson’s disease (PD), Lewy body dementia (LBD), Multiple System Atrophy (MSA), and Alzheimer’s disease concurrent with LBD (AD-LBD). These disorders are unified by a pathological hallmark: aberrant misfolding and accumulation of α-synuclein (α-syn). This review delves into the pivotal role of α-syn, the key agent in α-synucleinopathy pathophysiology, and provides a survey of potential therapeutics that target cell-to-cell spread of pathologic α-syn. Recognizing the intricate complexity and multifactorial etiology of α-synucleinopathy, the review illuminates the potential of various membrane receptors, proteins, intercellular spreading pathways, and pathological agents for therapeutic interventions. While significant progress has been made in understanding α-synucleinopathy, the pursuit of efficacious treatments remains challenging. Several strategies involving decreasing α-syn production and aggregation, increasing α-syn degradation, lowering extracellular α-syn, and inhibiting cellular uptake of α-syn are presented. The paper underscores the necessity of meticulous and comprehensive investigations to advance our knowledge of α-synucleinopathy pathology and ultimately develop innovative therapeutic strategies for α-synucleinopathies. Graphical Abstract